Pour en finir avec l'ethnicité des objets - Peressini, Mauro (Anthropologica, 2022)
This paper suggests that the problem of research, within a museal institution, cannot be reduced to a simple question of vulgarization, that is of translation and communication of knowledge. It is also and foremost a problem of more or less incompatibility between different types of knowledge. Starting from a given case, the author analyzes how various sectors of the "museal world" tend to reduce the museum to an ethnocultural representation function and to produce a discourse on objects which are interpreted through assignments of origins, functions, meanings and values in accordance with a game of ethnic promotion and competition. Opposing this type of discourse, which transforms the museum in an agent of the confronting visions, the author proposes another type of discourse on objects which, rather than transforming them in representatives of ethno-national "cultures," considers them as products of a concrete social experience and thus avoids the traps associated with the ethnicization of objects.